Close encounters between Bible and film : an interdisciplinary engagement - Copier, Laura; Vander Stichele, Caroline (Semeia studies., 2016)
"This volume showcases the divergent approaches from film studies and cultural studies that can be used in the visual analysis of biblical and religious themes, narratives, and characters in cinema. It is the first volume that specifically addresses issues of methodology, theory and analysis in the study between bible and film. As such, this collection is of interest to scholars in Film Studies and Theology/Religion/Biblical Studies, who are invested in doing interdisciplinary research in the expanding field of religion and film"--